Fourth Interlinguistic Symposium - Koutny, Ilona; Stria, Ida (Język. Komunikacja. Informacja, 2019)
The fourth international Interlinguistic Symposium organised by the Interlinguistic Studies Programme (Institute of Linguistics, Faculty of Modern Languages and Literature, Adam Mickiewicz University, Poznań, Poland) was held September 21-22, 2017 in Poznań. The main subject was: The role of international languages from the time of Zamenhof to the modern multicultural world.